Prevalence, Awareness, Treatment, and Control of Hypertension Among Saudi Adults: A Secondary Analysis of National Health Survey Data Aligned With WHO Global Hearts Initiative Targets - Ahmed A. Almohammadi (University of Bisha Journal for Basic and Applied Sciences, 2026)
Background: Hypertension is the leading modifiable risk factor for cardiovascular disease and premature mortality globally. Despite its high prevalence in Saudi Arabia, the national hypertension care cascade—spanning awareness, treatment, and blood pressure control—remains insufficiently characterized across demographic and geographic strata.Objectives: To characterize the prevalence, awareness, treatment, and control of hypertension among Saudi adults, analyze temporal trends from 2013 to 2022, evaluate demographic and geographic variation, and assess alignment with WHO Global Hearts Initiative targets.Methods: This cross-sectional descriptive study analyzed secondary data from the Saudi Health Interview Surveys (2013, 2018), WHO Global Health Observatory estimates, and Ministry of Health Annual Statistical Yearbooks (2013–2022). Hypertension was defined as systolic blood pressure ≥ 140 mmHg and/or diastolic ≥ 90 mmHg or current antihypertensive medication use. The hypertension care cascade was assessed across prevalence, awareness, treatment, and control metrics. Descriptive statistics characterized patterns; comparative analysis evaluated alignment with WHO Global Hearts Initiative targets (≥ 80% awareness, treatment, and control among hypertensive individuals).Results: Hypertension prevalence increased from 27.6% (95% CI: 26.8–28.4%) in 2013 to 34.2% (95% CI: 33.4–35.0%) in 2022. Among hypertensive adults in 2022, awareness reached 64.8% (95% CI: 63.6–66.0%), treatment 79.3% (95% CI: 78.0–80.6%) of aware individuals, and blood pressure control 46.1% (95% CI: 44.5–47.7%) of treated individuals. Males demonstrated higher prevalence (35.8%) but lower awareness (58.4%) than females (27.8%; 68.9%). Prevalence increased progressively with age, reaching 67.8% in adults aged ≥ 60 years. All five administrative regions demonstrated awareness and control rates below WHO Global Hearts Initiative targets. Only 8.1% of all Saudi adults had diagnosed, treated, and controlled hypertension.Conclusions: Saudi Arabia faces a growing and inadequately controlled hypertension burden. The largest gaps in the care cascade are at the awareness and control stages. Targeted screening, antihypertensive medication adherence support, and primary healthcare system strengthening are essential to approach WHO Global Hearts Initiative benchmarks and reduce cardiovascular disease mortality.